CLINICAL AND IMMUNOLOGICAL FEATURES OF TRANSIENT SYNOVITIS OF THE HIP JOINT AND DISEASE LEGG-CALVE-PERTHES IN CHILDREN OF EARLY AND SCHOOL AGE - Шабалдин, Никита Андреевич; Головкин, Сергей Иванович; Шабалдин, Андрей Владимирович (Mother and Baby in Kuzbass, 2017)
The study of disorders of systemic immunity and immune regulation in idiopathic transient synovitis of the hip joint (ITSHJ) and disease Legg-Calve-Perthes (DP) in children of early and school age. Studied 37 children with ITSHJ and 11 children with DP in the age interval of 3-12 years. The control group consisted of 29 healthy children. Investigated cytokine levels in the peripheral blood and the level of antibodies to conditionally pathogenic microflora. It is shown that ITSHJ and DP different in the immunopathogenesis of the disease. ITSHJ associated with allergic (atopic and immune) immune response to the antigens of pathogenic microorganisms and the herpes viruses and the development of infectious and allergic inflammation. DP associated with aseptic inflammation, developing on the background of high activity of IL-1Ra, TNF-a and induction of the rheumatoid factor. Pathogenetically justified in this pathology will be the appointment of drugs blocks the activity of TNF-a.
Keywords: the immune status; the transient synovitis of the hip joint; the Legg-Calve-Perthes disease; children